The Early Use of Selective Hemoadsorption Based on a Hyper-Crosslinked Styrene-Divinylbenzene Copolymer in Patients with Toxic Rhabdomyolysis Complicated by Acute Kidney Injury (Multicenter Randomized Clinical Trial) - S. V. Masolitin; D. N. Protsenko; I. N. Tyurin; M. A. Magomedov; T. G. Kim; L. A. Grishina; A. O. Bykov; Е. B. Gelfand; O. V. Ignatenko (Общая реаниматология)
Rhabdomyolysis (RM) is a clinical and laboratory syndrome with the underlying destruction of myocytes and the release of intracellular debris into the systemic circulation. In more than 55% of cases, RM is complicated by acute kidney injury (AKI), which necessitates various methods of extracorporeal detoxification and currently is a controversial issue.Aim: to improve the results of treatment of patients with RM of toxic origin complicated by AKI by using early selective hemoadsorption (SH).Material and methods. The study included 36 patients divided into 2 groups. Group 1 included 24 patients who received standard therapy and hemodiafiltration (HDF) as a life-saving intervention. Group 2 comprised 12 patients who underwent early SH to prevent the progression of AKI. We performed a comparative analysis of clinical and laboratory parameters and treatment outcomes in the groups.Results. The use of SH was associated with reduced level of myoglobin on day5 of therapy from 384.1 to 112.4 gg/l (70.7%) vs 335.15 to 219.1 gg/l (34.6%) reduction in the conservative therapy group. By day 7, this parameter was 18.8 (95.1%) and 142.4 (57.5%), respectively (7=0.012). The level of cystatin-C decreased on day 5 from 17.3 to 3.2 mg/l (81.5%) in group 2 and from 14.9 to 11.7 mg/l (21.5%) in group 1. By day 7, this parameter decreased to 2.5 (85.6%) and 14.1 (5.3%) mg/l, respectively (7=0.001). The length of ICU stay in group 2 was 7 (6; 9) days, while in the conservative therapy group it was 12 (7; 13) days (7=0.04). The hospital stay was 12 (10; 16) and 22 (14,5; 24,5) days, respectively (7=0.028).Conclusion. The early use of SH in the intensive therapy helped decrease the levels of markers of endogenous intoxication, AKI severity, improve the filtration capacity of the kidneys, and reduced the length of stay in the ICU and hospital.